Velocity distribution and sediment transport in two-stage channel - Lim, Siow Yong. (2008)
This project presents the results of studies involving two topics. The first is an experimental study on the velocity distribution and abutment scour in two-stage channels. The second involves a general study on the flow resistance laws governing flow in alluvial channels.